Immunohistological localisation of staphylococcal toxic shock syndrome toxin (TSST-1) antigen in sudden infant death syndrome. - Newbould, M J (1989)
A polyclonal antiserum to toxic shock syndrome toxin (TSST-1) and a standard immunoperoxidase technique were used on formalin fixed tissues from 50 cases of sudden infant death syndrome (SIDS) to determine if the syndrome was associated with bacterial infection. There was strong specific staining in the renal tubular cells in nine (18%) cases. A similar pattern of staining was seen in three of a series of 50 kidneys selected for comparison from a wide range of necropsy cases. The staining was finely granular within the cytoplasm of proximal convoluted tubular cells and diffuse in tubular cell nuclei. In an attempt to validate the staining pattern the immunoperoxidase technique was also performed on formalin fixed kidneys from rats which had been given intravenous injections of crude bacterial products containing TSST-1. These showed coarse granular cytoplasmic staining in proximal convoluted tubules with some diffuse nuclear staining. This pattern was not seen in controls injected with saline. These results indicate that TSST-1 might have a pathogenic role in some cases of SIDS.